2013
DOI: 10.1093/ehjci/jet014
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse myocardial fibrosis in the systemic right ventricle of patients late after Mustard or Senning surgery: an equilibrium contrast cardiovascular magnetic resonance study

Abstract: Septal interstitial expansion is seen in adults late after atrial redirection surgery for TGA. It correlates well with NT-proBNP and CI and may have a role in the development of RV systolic impairment. Measuring interstitial expansion in the RV free wall is difficult using this methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 34 publications
5
45
0
Order By: Relevance
“…We have previously suggested that patchy fibrosis ensues when a certain threshold of RV mass is reached, 1 and our current data showing that increased RV mass is associated with cardiac events support this hypothesis of ongoing pathological RV remodeling. As with previous crosssectional studies, we found that systemic RV fibrosis related to increased dilatation, 1,22,29,30 noninvasively determined RV wall stress and impaired systemic ventricular function. Initially, the increased pressure overload for a morphological RV in the systemic position can be compensated for by adaptive RV hypertrophy to preserve RV function and normalize RV wall stress related to dilatation.…”
Section: Rv Fibrosis and Its Independent Association With Clinical Ousupporting
confidence: 87%
“…We have previously suggested that patchy fibrosis ensues when a certain threshold of RV mass is reached, 1 and our current data showing that increased RV mass is associated with cardiac events support this hypothesis of ongoing pathological RV remodeling. As with previous crosssectional studies, we found that systemic RV fibrosis related to increased dilatation, 1,22,29,30 noninvasively determined RV wall stress and impaired systemic ventricular function. Initially, the increased pressure overload for a morphological RV in the systemic position can be compensated for by adaptive RV hypertrophy to preserve RV function and normalize RV wall stress related to dilatation.…”
Section: Rv Fibrosis and Its Independent Association With Clinical Ousupporting
confidence: 87%
“…The CMR T1 mapping approach allows for a noninvasive estimation of the myocardial fibrosis content. 10,13,14,24,25 In a small number of adult patients after HTx (n = 9), postcontrast T1 times correlated with myocardial collagen content. 26 Prolonged native T1 times, that is, before contrast application, and increased TBPC values by CMR both indicate increased diffuse myocardial fibrosis, in the absence of other conditions that expand the extracellular space, such as edema.…”
Section: Discussionmentioning
confidence: 98%
“…8,9 The technique has been validated extensively and used in a broad spectrum of congenital and acquired heart conditions in adults and children. [10][11][12][13][14] The aim of this study was (1) to quantify the degree of myocardial fibrosis in children after HTx in comparison with healthy controls and (2) to explore the impact of myocardial fibrosis on cardiac function.…”
mentioning
confidence: 99%
“…Patients with transposition of the great arteries and systemic right ventricle late after atrial redirection surgery had higher ECV in the interventricular septum as compared with controls, and ECV correlated with natriuretic peptide and cardiac index. 47 In children and adolescents with congenital aortic stenosis, ECV correlated with the degree of diastolic dysfunction. 53 Studies need to identify if an earlier intervention is able to prevent this chronic fibrotic burden, which is thought to ultimately affect myocardial function.…”
Section: Cmr Fibrosis Markers In Clinical Pediatric and Congenital Hementioning
confidence: 98%
“…Measurements in the right ventricle and in the atrium have been reported, but histological validation is lacking. [45][46][47] In adults, native T1 times and ECV increase with age. 44 Several, but not all, studies report CMR fibrosis markers to be higher in women than in men.…”
Section: Regional Differences In T1 Within the Heart And Sex And Age mentioning
confidence: 99%